Mengatur bebunyian di area urban di Indonesia - Christina Eviutami Mediastika; Anugrah Sabdono Sudarsono; Sentagi Sesotya Utami; Isnen Fitri; Rizka Drastiani; Maria Immaculata Ririk Winandari; Akbar Rahman; Asniawaty Kusno; Ni Wayan Meidayanti Mustika; Yuliana Bhara Mberu; Ressy Jaya Yanti; Zulfi Aulia Rachman (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Like other developing countries where traffic is a significant sound nuisance, traffic in Indonesian urban areas is boisterous. How this condition is regulated by the Indonesian government so that the community can live healthily and comfortably is a very crucial issue. Unfortunately, Indonesia has not had any sound environmental improvement since the regulation was enacted. Additionally, regulators and government officers who run the rule carelessly worsen the condition. This study aims to study how sound is regulated in Indonesia’s central and local governments, what types of sound or noise and levels are covered, and whether recent local regulations have been enacted to regulate sound in Indonesian cities. The study mainly uses quantitative, i.e., snowball or chain referral sampling techniques, to collect sound regulations applied in ten large and busy cities in Indonesia. Then, the qualitative stage was conducted based on the content of the rules. The data shows that the Indonesian government at both the central and regional levels does not have legal standing to regulate noise caused by the absence of noise regulation at the statutory level that can force those who violate the law to be punished. The only regulation is by the Minister of Environment, dated 1996, which is referenced nationally and adopted by most cities without or with minor modifications. This study found that (1) six of the ten cities regulate only one type of noise among various types of noise, (2) twelve of the 35 local regulations incorporate noise regulations into air pollution regulations instead of stand-alone regulations, (3) because provinces and cities adopt central regulations, the lowest noise level follows the central standard at 55 dB for settlement area without specific frequency ranges, (4) there is no straightforward procedure on how measurements to be carried out except in regulations stipulated by Yogyakarta province. There is also a fact that a standardized procedure for measuring noise is vital to be included in the regulation because unskilled government officials collected invalid data in dealing with a noise complaint leading to an unresolved situation.